2014
DOI: 10.1155/2014/580373
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis and New Trends by Ophthalmological Evaluation: A Pilot Study

Abstract: Background. Cystic fibrosis (CF) is characterized by hypoxia that affects several organic tissues. Retinal ganglion cells may suffer from the hypoxic status, and this may lead to alterations of retinal nerve fiber. Methods. Twenty-two eyes in CF patients were analyzed. A complete ocular evaluation and visual field exams of the 30 central degrees were performed using the frequency doubling technology (FDT). Forced expiratory volume in one second (FEV1%), forced vital capacity (FVC%), oxyhaemoglobin saturation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Our finding of no statistically significant difference in IOP measurements between CF patients and controls, is in accordance with a previous CF study. 18 This finding is pathophysiologically supported by other studies that demonstrated no contribution by the CFTR protein to aqueous humor production. 28,29 Our study comes with certain limitations, including lack of information on other parameters assessing nerve fiber loss, both anatomical (ganglion cell layer, cell-inner plexiform layer, and cell complex) and functional (visual fields).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our finding of no statistically significant difference in IOP measurements between CF patients and controls, is in accordance with a previous CF study. 18 This finding is pathophysiologically supported by other studies that demonstrated no contribution by the CFTR protein to aqueous humor production. 28,29 Our study comes with certain limitations, including lack of information on other parameters assessing nerve fiber loss, both anatomical (ganglion cell layer, cell-inner plexiform layer, and cell complex) and functional (visual fields).…”
Section: Discussionsupporting
confidence: 75%
“…15,16 Pathophysiological studies demonstrate temporary optic nerve hypoperfusion, potentially due to the afore-described mechanisms. 17 In relevance to CF, where lung function is also impaired, Nebbioso et al 18 performed visual field examination by Humphrey Frequency Doubling Technology (FDT) and observed lowered average responses in the nasal-inferior sector of patients versus controls, as well as abnormal glaucoma hemifield test (GHT) and mean deviation at FDT perimetry. These results were assumed to be a consequence of the pulmonary disease causing long term hypoxia and vascular dysregulation in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In retinal diseases, fibrosis leads to changes in retinal tissues and retinal ischemic conditions, including inflammation, ischemia, and neurodegeneration 18 . The expression of TGF‐β, MMP‐9, and Snail increased after 7 days post vascular occlusion (Figure 1A–D).…”
Section: Discussionmentioning
confidence: 98%
“…It can be concluded that hypoxia caused by cystic fibrosis may decrease the optic nerve activity. 17 A similar mechanism of optic nerve involvement can be considered for COPD patients as both sufferers endure chronic hypoxia due to lung disorders.…”
Section: Discussionmentioning
confidence: 99%